Indigenous knowledge documentation: perspectives of Dusun and Bajau communities in Kota Belud, Sabah, Malaysia - Adam, Anis Amalina; Othman, Normala; Ab. Halim, Adlina (Human Resource Management Academic Research Society, 2022)
In the context of biodiversity conservation, the application of indigenous knowledge provides insights into how indigenous peoples operate and coexist with the natural environment without imposing severe impacts and essentially sustain the resources for generations. Due to its oral and practical nature in transmission, indigenous peoples find it difficult to maintain the traditional pathway of indigenous knowledge transfer. Moreover, indigenous knowledge is perceived to be extinct sooner or later. This phenomenon calls for indigenous knowledge documentation. This study aimed to explore the perspectives of the Dusun and Bajau people with regard to documentation of their indigenous knowledge. This study applied qualitative research design, which was carried out in Kota Belud, Sabah. Semi-structured interviews were employed to collect primary data with six informants (n = 6). The data was then thematically analysed with the aid of Nvivo 10. The findings in this study revealed that the informants acknowledged that indigenous knowledge gradually vanished. Following that, they expressed a positive attitude pertaining to the documentation of indigenous knowledge. At the same time, informants conveyed some of the possible constraints in documenting indigenous knowledge, such as biopiracy, lack of support from authorities, and lack of initiatives among indigenous peoples. Finally, this study concludes by presenting some recommendations to address the issues of indigenous knowledge documentation.